The Effectiveness of Group Guidance with A Symbolic Modeling Technique to Improve Students’ Career Maturity - Wahyudi, Mohammad Chandra; Eddy Wibowo, Mungin; Saraswati, Sinta (Universitas Negeri Semarang, 2023)
Career maturity is the initial step to achieving career success that is truly needed by adolescents to choose and prepare themselves to enter the world of work well. Thus, this study strived for determining the effectiveness of group guidance with a symbolic modelling technique to improve the career maturity of grade twelve students at SMK Negeri 1 Muara Wahau. It was experimental research which used a pretest-posttest comparison group design and involved 8 students in twelfth grade chosen using a purposive sampling technique of 145 population. They were taught using a symbolic modelling technique for seven sessions. Findings showed that the symbolic modelling technique has been effective to improve the career maturity of the twelfth graders at SMK Negeri 1 Muara Wahau. This finding can be an implication for the implementation of group counselling services at Islamic boarding schools.